The use of CRM for Customer Management at Cellular Telecommunications Industry - Ayu Kartika Puspa (International Conference on Engineering and Technology Development (ICETD), 2013)
At this time the telecommunications not only as part of the lifestyle but have become an important necessity in everyday life. Requirement will result in the proliferation of communications service providers with a variety of rates and offer to potential customers. While the numbers show the loss of customers is also increasing, most customers only a short time on a single provider. Service providers are not only competing to gain new customers but also retain the loyalty of existing customers. CRM Data Mining using a proper solution to target new markets or retain existing customers.